Preserving Local Crafts of Malaysian Tangible Cultural Heritage Through Travel Kits by State Identity - Zainun, Muhammad Rohaizad; Kamaruddin, Norfadilah (Research in Management of Technology and Business, 2024)
Many reasons are contributing to the growing need for cultural heritage preservation including development, modernization, climate change, and assimilation. Within this, it is important to emphasized that cultural heritage tourism encompasses not only intangible heritage, such as traditions, values, and religions, but also tangible heritage, such as craft, materials, and settlement patterns. Craft has a unique quality and also serves as a powerful means of cultural communication in the community. By classifying the new tourism goods based on traditional crafts according to their different states, this research examined the types and significance of traditional crafts as well as the attitudes of local citizens towards them, with the goal of preserving Malaysia’s cultural legacy. The results from the study established the justification for preserving Malaysia’s cultural heritage through two major points: the responsibility of the current generation, the potential design according to state identity as part of cultural preservation and the relevancy of preserving and maintaining Malaysia’s cultural history to a tourism product.